Självomsorg- Hälso- och sjukvårdskuratorers omsorg om sig själv i arbete med kris och trauma - Rudqvist,Annika (2023)
The aim of this study was to gain knowledge about which self-care strategies are used by health care counselors who work with patients in crisis or patients who have experienced trauma. To do so there was also a need to gain knowledge about stressful or emotional challenges the health care counselors experience in the daily work. The method used was a case study with semi-structured interviews. Six health care counselors working at a counselor’s reception at a hospital in Skåne, Sweden participated. The study has its basis in emotion theory, coping theory, KASAM and salutogenes. Qualitative content analysis has been used to analyze the collected empirical data. The result shows that self-care is understood by the health care counselors as a self-attitude embracing self-awareness and self-compassion. Empathic distance, emotional distance through physical distance and reflection on one´s own or with colleagues are found as self-care strategies. Work experience appear to be the main source of knowledge about self-care strategies.
Keywords: Self-care; strategies; coping; professional; health care counselor